Inducing Somatic Symptoms in Functional Syndrome Patients: Effects of Manipulating State Negative Affect. Issue 9 (November 2017) - Van Den Houte, Maaike; Bogaerts, Katleen; Van Diest, Ilse; De Bie, Jozef; Persoons, Philippe; Van Oudenhove, Lukas; Van den Bergh, Omer
ABSTRACT: Objective: Induction of negative affective states can enhance bodily symptoms in high habitual symptom reporters among healthy persons and in patients with irritable bowel syndrome. The aims of this study were to replicate this effect in patients with fibromyalgia and chronic fatigue syndrome and to investigate the role of moderators, focusing on alexithymia, negative affectivity, and absorption. Methods: Patients with fibromyalgia and/or chronic fatigue syndrome ( n = 81) and HCs ( n = 41) viewed series of neutral, positive, and negative affective pictures. After every picture series, participants filled out a somatic symptom checklist and rated emotions experienced during the picture series on valence, arousal, and perceived control. Results: Patients reported more somatic symptoms after viewing negative pictures (least square mean [LSM] = 19.40, standard error (SE) = 0.50) compared with neutral (LSM = 17.59, SE = 0.42, p < .001) or positive (LSM = 17.04, SE = 0.41, p < .001) pictures, whereas somatic symptom ratings of HCs after viewing negative picture series (LSM = 12.07, SE = 0.71) did not differ from ratings after viewing neutral (LSM = 11.07, SE = 0.59, p = .065) or positive (LSM = 11.10, SE = 0.58, p = .93) pictures. Negative affectivity did not moderate the symptom-enhancing effect of negative affective pictures, whereas the alexithymia factor "difficulty identifying feelings" and absorption did ( p = .016 and p = .006, respectively). Conclusion: Negative affective states elicit elevated somatic symptom reports in patients experiencing fibromyalgia and/or chronic fatigue syndrome. This symptom-enhancing effect is greater in patients having higher difficulty to identify feelings and higher absorption scores. The results are discussed in a predictive coding framework of symptom perception.